Epidural Analgesia Improves Postoperative Pain Control but Impedes Early Discharge in Patients Undergoing Pancreatic Surgery. Issue 5 (May 2019) - Kim, Stephanie S.; Niu, Xiaojuan; Elliott, Irmina A.; Jiang, Jerry P.; Dann, Amanda M.; Damato, Lauren M.; Chung, Hallie; Girgis, Mark D.; King, Jonathan C.; Hines, O. Joe; Rahman, Siamak; Donahue, Timothy R.
Abstract : Objectives: The aim of this study was to evaluate the impact of epidural analgesia (EA) on postoperative length of stay (LOS), expeditious discharge, and pain relief after pancreaticoduodenectomy (PD) and distal pancreatectomy (DP). Methods: Retrospective reviews of 2014–2015 American College of Surgeons National Surgical Quality Improvement Program databases and our institutional pancreatic surgery database were conducted. Results: On univariate analysis, EA was associated with statistically significant longer lengths of stay for both PD and DP. On comparative analysis at mode LOS, discharged before versus after 7 days for PD and 6 days for DP, EA was a significant predictor for the longer groups for both procedures on multivariable analysis (PD, odds ratio of 1.465, P < 0.001; DP, odds ratio of 1.471, P = 0.004). On review of our institution's pancreatic surgery database, patient-reported pain scores were significantly lower in the EA groups than intravenous narcotics groups on the day of surgery only for both PD and DP. Conclusions: Epidural analgesia was associated with longer LOS with a most pronounced effect on early discharge after surgery for patients undergoing open PD and DP. It only resulted in superior pain control on the day of surgery.